Evaluasi Program Surabaya Green And Clean Berbasis Sustainable Development (Studi pada Dinas Kebersihan dan Pertamanan Kota Surabaya. - Vinna Kumalasari (Jurnal Administrasi Publik, 2015)
Abstract: Evaluation of Surabaya Green and Clean Program Based on Sustainable Development (Study in Department Hygiene and Landscape Gardening of Surabaya City). This study is based on the existing problems in the current era of increasingly complex, not only environmental issues but also development issues, through a waste management program that is community-based self-Surabaya Green and Clean. Where this program invites the participation of the community to manage garbage in creating an environment that is livable through the concept of sustainable development or environmental sustainable development in the city of Surabaya. The research uses descriptive research with a qualitative approach In this study, researchers have three research focus, namely: 1). Implementation of Surabaya Green and Clean program in Surabaya which includes actors in the SGC program, budget and human resource support, program management mechanism SGC and SGC program benefits 2). Achievement of Surabaya Green and Clean the implications for the concept of Sustainable Development. 3) inhibiting factors and the factors supporting the implementation of Surabaya Green and Clean program.   Keywords : Surabaya Green and Clean, Sustainable Developmen, evaluation program Abstrak: Evaluasi Program Surabaya Green And Clean Berbasis Sustainable Development (Studi pada Dinas Kebersihan dan Pertamanan Kota Surabaya. Penelitian ini dilandasi oleh masalah yang ada dalam era saat ini yang semakin kompleks, tidak hanya masalah lingkungan saja tetapi juga masalah pembangunan, melalui sebuah program pengelolaan sampah mandiri berbasis komunitas yaitu Surabaya Green and Clean. Dimana program ini mengajak partisipasi masyarakat untuk mengelola sampah dalam menciptakan lingkungan yang layak-huni melalui konsep sustainable development atau pembangunan berkelanjutan berwawasan lingkungan di Kota Surabaya. Dalam penelitian ini peneliti mempunyai tiga fokus penelitian, yaitu: 1). Pelaksanaan program Surabaya Green and Clean di Kota Surabaya yang meliputi aktor dalam program SGC, anggaran dan dukungan sumber daya manusia, mekanisme pelaksanaan program SGC, dan manfaat program SGC  2). Capaian dari SGC yang berimplikasi pada konsep Sustainable Development. 3) Faktor penghambat dan factor pendukung pelaksanaan program SGC.   Kata kunci: surabaya green and clean, sustainable development, evaluasi program